Unraveling the unexpected: A rare case of filariasis in chronic myeloid leukemia with a review of the literature - Nikhil Kumar (Tungs’ Medical Journal)
Filariasis poses a significant public health challenge in tropical and subtropical regions. Incidental occurrences of filariasis in peripheral smears among patients with hematological malignancies are rarely documented. Here, we report a case of chronic myeloid leukemia in the chronic phase associated with Wuchereria bancrofti. This case report highlights the importance of meticulous examination of peripheral blood smears to detect microfilaria, even in the absence of clinical features commonly associated with filariasis, especially in patients from regions where the disease is prevalent.